Prevalence and neonatal outcomes of preterm born at Garissa county referral hospital, Kenya - Amolo, Tom; Olayo, Rose; Otieno, Walter; Esendi, Gladys C.; Raballah, Evans (International Journal Of Community Medicine And Public Health, 2024)
Background: Despite the significance of late preterm and early term neonates in neonatal health, comprehensive data on their prevalence, morbidity, mortality, and associated maternal sociodemographic and economic characteristics is grossly lacking in Garissa County, Kenya. This study aimed to determine the prevalence, morbidity, and mortality of late preterm (LPN) and early term neonates (ETN) born at Garissa County Referral Hospital (GCRH), relative to full-term neonates (FTN). Methods: Singleton live neonates in the three groups were enrolled. Prevalence was computed as percentages of births in each category relative to total singleton live births during the study period. Ordinal logistic regression analysis was used to assess morbidity patterns, with statistical significance set at p<0.05. Mortality rates were presented as total deaths per 1,000 live births within the first 28 days. Results: The LPN, ETN, and FTN had a prevalence of 8.47%, 11.86%, and 9.2%, respectively. Maternal age was significantly associated with gestational age (p=0.014; Φc=0.263), while other sociodemographic and economic characteristics were comparable across groups (p>0.05). LPNs had lower odds of respiratory distress diagnosis on day 1 compared to ETNs (OR=-1.68896; 95% CI: -3.012335 to -0.365593; p=0.012). Mortality rates were comparable among gestational age categories (p=0.649). Conclusions: Overall, the study shows that LPN and ETN are considerably prevalent in Garissa County and that, only maternal age impacts on gestational age. Targeted interventions, particularly for younger mothers, should be implemented to mitigate associated risks and improve neonatal outcomes.